Molecular survey and genetic characterization of ‘Candidatus Mycoplasma haemolamae’ in llamas (Lama glama) and alpacas (Vicugna pacos) from Southern Chile. - Ramos, Patricio; Sepulveda-Garcia, Paulina; Alabí, Amir [UNESP]; Romero, Alex; Pinto, Teresa; Rojas, Alejandro; Bittencourt, Pedro; Müller, Ananda (Elsevier, 2021)
This study aimed to perform a molecular survey and identification of hemotropic Mycoplasma spp. in domestic South American Camelids from Southern Chile. Conventional PCR (cPCR) for hemotropic Mycoplasma spp. based on 16S rRNA gene (620bp fragment) was performed in 87 EDTA-blood samples taken from 48 llamas (Lama glama) and 39 and alpacas (Vicugna pacos) from to Temuco, La Araucanía region and Valdivia, Los Rios region, Southern Chile. 16S rRNA hemotropic Mycoplasma PCR-positive were sequenced for species identification, phylogenetic and haplotype analyses, and further tested by cPCR targeting a fragment (160-210 bp) of the RNaseP (rnpB) gene. Based upon 16S rRNA cPCR results, the overall hemotropic Mycoplasma spp. occurrence in Southern camelids was 9.2% (8/87 [95% CI (4.0–17.3%)]), with five positive alpacas (12.8%; 5/39 [95% CI (4.3–27.4%)]) and three llamas (6.3%; 3/48 [95% CI (1.7–17.2%)]). All 16S rRNA PCR-positive samples were negative for the rnpB gene. Obtained 16S sequences presented high identity (99-100%) by BLASTn analysis to ‘Candidatus Mycoplasma haemolamae’ from an alpaca in the United Kingdom. Phylogenetic and haplotype analyses of the 16s rRNA gene showed high similarity among ‘Candidatus M. haemolamae’ sequences of this study and the ones from North America, Europe, and Asia evidencing a low diversity of Chilean samples, with only one haplotype detected (#1). Haplotype #1 from South American Camelids in Chile was worldwide distributed and observed in North America, Europe, and Asia. ‘Candidatus M. haemolamae’ detected for the first time in South American camelids in Southern Chile had low diversity and was worldwide spread.
Keywords: Camelids; Hemoplasma; Hemotropic Mycoplasma spp.; PCR; South America